2016
DOI: 10.1111/nyas.13018
|View full text |Cite
|
Sign up to set email alerts
|

New strategies to target iron metabolism for the treatment of beta thalassemia

Abstract: Iron is one of the most abundant elements in the Earth and a fundamental component of enzymes and other proteins that participate in a wide range of biological processes. As the human body has no mechanisms to eliminate excessive iron, its metabolism needs to be tightly controlled in order to avoid all the sequelae associated with high iron levels. Iron overload is the main cause of morbidity and mortality in beta thalassemia. The master regulator of iron homeostasis, hepcidin, is chronically repressed in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 92 publications
0
26
0
Order By: Relevance
“…Phenotypes of thalassemia and their severity can be characterized according to dependence on blood transfusions. Patients are conventionally described as having transfusion‐dependent thalassemia (TDT; β‐thalassemia major) when they have a life‐long requirement for regular transfusions, which results in iron overload . Chronic transfusions are not essential for those with non‐transfusion‐dependent thalassemia (NTDT; β‐thalassemia intermedia) to survive, but for limited periods of time, infrequent or sometimes repeated transfusions might be necessary .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenotypes of thalassemia and their severity can be characterized according to dependence on blood transfusions. Patients are conventionally described as having transfusion‐dependent thalassemia (TDT; β‐thalassemia major) when they have a life‐long requirement for regular transfusions, which results in iron overload . Chronic transfusions are not essential for those with non‐transfusion‐dependent thalassemia (NTDT; β‐thalassemia intermedia) to survive, but for limited periods of time, infrequent or sometimes repeated transfusions might be necessary .…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the amount of released iron exceeds the binding capacity of transferrin and non‐transferrin‐bound iron (NTBI) is formed in the circulation . Due to its ability to generate reactive‐oxygen species, accumulation of unbound iron in tissues can be toxic, resulting in tissue injury (including trophic skin changes and leg ulcers), organ dysfunction (including liver disease, heart failure and endocrinopathies), and death …”
Section: Introductionmentioning
confidence: 99%
“…The use of once daily dosage of deferasirox is more likely to be resulted in the improvement in patients adherence to medication. 11 In this study, the assessment of side effect was performed by conducting the interview with participants using the Naranjo scale. Within the Naranjo scale, there were 10 questions related to the adverse events experienced by the patiens during the therapy.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that administration of these molecules in a thalassemic mouse model results in reduced iron absorption and increased iron retention in splenic macrophages [61]. Induction of iron restriction by means of transferrin infusions, prevents iron overload, redistributes iron from parenchymal cells to macrophage stores, and partially controls anemia in βthalassemic mice [63].…”
Section: Improving Iron Dysregulationmentioning
confidence: 99%